Sandstone-conglomerate rocky forms – more than a tourist attraction - Strzeboński, Piotr (Geotourism/Geoturystyka, 2018)
Natural, thrown open to the sightseeing rockies are undoubtedly a tourist attraction, but furthermore they constitute a precious source of geological and geomorphological information. A special scientific-cognitive and teaching value of the rocky forms is based on the possibility of carrying out direct observations on the character of deposits and on shaping these forms by exogenic processes. A good example of the rocky forms with such values is represented by sandstone-conglomerate rockies in the Outer Carpathians. One of the regions where such rockies occur is the Wiśnicz Foothil, where, among others, the Brodziński Stones (after a poet), the Mushroom Stone (after a mushroom-like shape) and the Chronowskie Tors (after the Chronów town) are localized. The Mushroom Stone serves to demonstrate general, common features of the origin of the rocky forms from the Istebna Beds (the Istebna Formation) observed by the author also in the Moravian Beskid Mts. and Silesian Beskid Mts. and the Small Beskid Mts. Epigenetic arcade structures, cellular structures (honey comb structures) and bowl structures form characteristic relief of rockies. The rocky forms have a complex origin, resulting from many interconnected factors and processes that develop in time with various intensity.